Multiple epitopes of hepatitis B virus surface antigen targeted by human plasma‐derived immunoglobulins coincide with clinically observed escape mutations. Issue 2 (26th August 2021) - Tarafdar, Sreya; Virata, Maria Luisa; Yan, Hailing; Zhong, Lilin; Deng, Lu; Xu, Yanqun; He, Yong; Struble, Evi; Zhang, Pei
Abstract: Hepatitis B immune globulin (HBIG) is a human plasma‐derived immunoglobulin G concentrate that contains a high titer of neutralizing antibodies (anti‐HBs) to the hepatitis B virus (HBV) surface antigen (HBsAg). HBIG is known to be highly effective in treating HBV infections, however, a more systematic characterization of the antibody binding sites on HBsAg and their correlation with emerging "escape" mutations in HBsAg was lacking. By using anti‐HBs antibodies from HBIG lots to screen random peptide phage display libraries, we identified five clusters of peptides that corresponded to five distinct anti‐HBs binding sites on the HBsAg. Three sites, Site II (C121‐C124), Site III (M133‐P135), and Site IV (T140‐G145), were mapped within the "a" determinant, while the two other sites, Site I (Q101‐M103) and Site V (I152‐S154), were outside the "a" determinant. We then tested in binding assays HBsAg peptides containing clinically relevant mutations previously reported within these sites, such as Y134S, P142S, and G145R, and observed a significant reduction in anti‐HBs binding activity to the mutated sites, suggesting a mechanism the virus may use to avoid HBIG‐mediated neutralization. The current HBIG treatment could be improved by supplementing it with site‐specific neutralizing monoclonal antibodies that target these mutations for control of HBV infections.